2021
DOI: 10.1088/1361-6439/abe09a
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the co-axial dispensing nozzle of a 3D bioprinter for the fabrication of tubular structures with micro-channel encapsulation

Abstract: The 3D bio-printing has been developed as an effective approach to artificially create tubular tissue structures, which have been frequently found in body and organ systems. China Agricultural University (CAU) has developed a laboratory 3D bio-printer that can create tubular structures with the encapsulation of microfluidic channel. In order to create a tubular structure with more effective micro-channel encapsulation for better nutrient delivery and chemical stimulation, this work presents a design optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Gelatin is also easily degraded in the body, making it suitable for bioprinting [26]. Shaoping et al demonstrated that a mixture of alginate and gelatin solution can produce bio-ink with a wide range of viscosity, from almost 0-25 000 mPa.s, compared to pure alginate or gelatin solutions (0% gelatin or 0% alginate) [25]. Therefore, this study employed an alginate-gelatin solution to produce a highviscosity printing material for improved formability.…”
Section: Experiments Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin is also easily degraded in the body, making it suitable for bioprinting [26]. Shaoping et al demonstrated that a mixture of alginate and gelatin solution can produce bio-ink with a wide range of viscosity, from almost 0-25 000 mPa.s, compared to pure alginate or gelatin solutions (0% gelatin or 0% alginate) [25]. Therefore, this study employed an alginate-gelatin solution to produce a highviscosity printing material for improved formability.…”
Section: Experiments Preparationmentioning
confidence: 99%
“…The outer shell fluid, which contains supporting material, and the inner core fluid, mixed with cells, merge at the exit end of the external needle, resulting in encapsulation. The core fluid, containing cells, is firmly wrapped by the shell layer fluid, resulting in microencapsulation [25]. This process is significant for improving cell viability and the performance of micro tubular structures.…”
Section: Piston-actuated Bio-printer Setupmentioning
confidence: 99%
“…These differences were taken into consideration during the set-up of the print flow rates for alginate and crosslinking inks. According to the properties of both alginate and crosslinking inks [32], the flow rates were fixed at 50 µL/min and at 100 µL/min, respectively.…”
Section: Rheological Studiesmentioning
confidence: 99%
“…The experiment devices of two-phase flow in microchannel consisted of the fluid driving unit, the microchannel sample, and the observation unit (Figure 1). The microchannel sample was vertical and coaxial [19,20], in which the dispersed phase flowed in the inner tube with the NaAlg solution and the continuous phase flowed in the outer tube with Oil. The inner diameters of the outer tube and the inner tube, respectively, were 1 mm and 0.42 mm.…”
Section: Experiments and Simulationmentioning
confidence: 99%
“…There were four group experiments with the different mass fraction of NaAlg solution (0.1 wt%, 0.5 wt%, 1.0 wt% and 1.5 wt%). The experiment parameters were in the The microchannel sample was vertical and coaxial [19,20], in which the dispersed phase flowed in the inner tube with the NaAlg solution and the continuous phase flowed in the outer tube with Oil. The inner diameters of the outer tube and the inner tube, respectively, were 1 mm and 0.42 mm.…”
Section: Experiments and Simulationmentioning
confidence: 99%